ANALISIS PERBANDINGAN PENGUNGKAPAN ISLAMIC SOCIAL REPORTING (ISR) ANTARA BANK UMUM SYARIAH DENGAN UNIT USAHA SYARIAH - Mukhti, Eriko Chiesa; Putra, Purnama (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2024)
This study aims to analyze the comparative disclosure of Islamic Social Reporting (ISR) between Islamic Commercial Banks (BUS) and Islamic Business Units (UUS). The research employs a descriptive quantitative method, with a sample of 7 Islamic Commercial Banks and 8 Islamic Business Units from 2018 to 2022. The results show a dominance of the employee theme, accounting for 26% for BUS and 29% for UUS. Community disclosure reaches 19% for both. The themes of products, services, and corporate governance range from 16-20%, while the lowest themes are financing and investment for BUS at 8% and the environment for UUS at 9%. BUS tends to disclose corporate social and environmental responsibilities more in-depth, while UUS focuses more on Sharia compliance and profit achievement. The difference in organizational structure explains the influence of company size on ISR in BUS, which is not significant in the more straightforward structure of UUS. Different social responsibility objectives and policies between BUS (focused on Sharia concepts) and UUS (following parent company policies) also play a role. The differing perspectives of the community at the locations of BUS and UUS can influence factors in social responsibility decision-making. This study highlights the complexity of ISR in the context of Islamic banking and provides insights into the development of policies and practices of social responsibility in this sector. It contributes to the literature on ISR disclosure in the Islamic banking sector and can serve as a reference for banks and Islamic business units to enhance their ISR disclosures.